Konflik sebagai Sumber Belajar Penguatan Literasi Sejarah dan Kesadaran Sosial Siswa di Wilayah Pesisir Halmahera Timur - Syahrir Ibnu; Dwi Sumaiyyah Makmur (LOSARI: Jurnal Pengabdian Kepada Masyarakat, 2026)
Limited historical literacy and social awareness remain challenges in strengthening students' character education, particularly in areas with complex social dynamics. This community service program aimed to enhance students' historical literacy and social awareness through local conflict-based learning at SMA Negeri 4 East Halmahera Regency. Local conflict was utilized as a contextual learning resource that promotes tolerance, peace, solidarity, and peaceful conflict resolution. The program employed an educational-participatory approach, including socialization, discussions, case studies, Focus Group Discussions (FGDs), student worksheets, reflection, and evaluation. The results showed a significant improvement in students' understanding of the causes and impacts of local conflicts, increasing from 34.3% before the program to 88.6% afterward. Students also demonstrated stronger historical thinking skills, greater social empathy, and increased awareness of unity, dialogue, and tolerance in a multicultural society. These findings indicate that local conflict can serve as an effective contextual and reflective learning resource for strengthening historical literacy and character education.